IoT and Renewable Energy Training and Implementation for Smart Village in Karang Anyar - Purwono Prasetyawan; Putty Yunesti; Afit Miranto; Doni Bowo Nugroho; Gde KM Atmajaya; Meraty Ramadhini; Muhammad Reza Kahar Aziz; Eko Satria (Journal Social Science And Technology For Community Service, 2026)
This community service program addressed productivity instability in oyster mushroom cultivation and limited utilization of digital and renewable-energy-based village infrastructure in Karang Anyar Village, South Lampung. The program aimed to strengthen agricultural productivity and support Smart Village development through training and implementation of Internet of Things (IoT) and renewable energy technologies. The activities included participatory needs assessment, installation of an IoT-based automatic misting system in mushroom houses, deployment of solar-powered lighting systems for the village sports field, and training on Content Management System (CMS)-based website management involving mushroom farmers, village administrators, and university students participating in the Community Service Program (KKN). Functional testing showed that the IoT-based misting system achieved 100% operational performance, while training activities involved seven mushroom farmers with more than 50% of participants demonstrating adequate understanding of system operation and digital platform utilization. In addition, the installation of solar-powered lighting improved the accessibility of village sports facilities at night. These results demonstrate that integrating IoT and renewable energy technologies effectively supports Smart Village development and strengthens sustainable community-based innovation in rural areas.